A Novel Cecropin-LL37 Hybrid Peptide Protects Mice Against EHEC Infection-Mediated Changes in Gut Microbiota, Intestinal Inflammation, and Impairment of Mucosal Barrier Functions - Wei, Xubiao; Zhang, Lulu; Zhang, Rijun; Koci, Matthew; Si, Dayong; Ahmad, Baseer; Cheng, Junhao; Wang, Junyong; Aihemaiti, Maierhaba; Zhang, Manyi (Frontiers in Immunology, 2020)
Intestinal inflammation can cause impaired epithelial barrier function and disrupt immune homeostasis, which increases the risks of developing many highly fatal diseases. Enterohemorrhagic Escherichia coli (EHEC) O157:H7 causes intestinal infections worldwide and is a major pathogen that induces intestinal inflammation. Various antibacterial peptides have been described as having the potential to suppress and treat pathogen-induced intestinal inflammation. Cecropin A (1–8)-LL37 (17–30) (C-L), a novel hybrid peptide designed in our laboratory that combines the active center of C with the core functional region of L, shows superior antibacterial properties and minimized cytotoxicity compared to its parental peptides. Herein, to examine whether C-L could inhibit pathogen-induced intestinal inflammation, we investigated the anti-inflammatory effects of C-L in EHEC O157:H7-infected mice. C-L treatment improved the microbiota composition and microbial community balance in mouse intestines. The hybrid peptide exhibited improved anti-inflammatory effects than did the antibiotic, enrofloxacin. Hybrid peptide treated infected mice demonstrated reduced clinical signs of inflammation, reduced weight loss, reduced expression of pro-inflammatory cytokines (tumor necrosis factor-alpha (TNF-), interleukin-6 (IL-6), and interferon-gamma (IFN-)), reduced apoptosis, and reduced markers of jejunal epithelial barrier function. The peptide also affected the MyD88–nuclear factor B signaling pathway, thereby modulating inflammatory responses upon EHEC stimulation. Collectively, these findings suggest that the novel hybrid peptide C-L could be developed into a new anti-inflammatory agent for use in animals or humans.